Australia’s Big Gamble: The News Media Bargaining Code and the Responses from Google and Facebook - Bailo, Francesco; Meese, James; Hurcombe, Edward; Leaver, Tama; Bruns, Axel; Angus, Daniel; Barnet, Belinda (2021)
Responding rapidly to extraordinary developments in early 2021, this panel examines the background, development, implementation, and consequences of the latest Australian regulatory intervention in the engagement between content platforms and domestic media organisations: the News Media Bargaining Code (NMBC). The Australian federal government envisioned the NMBC as “a mandatory code of conduct to address bargaining power imbalances between Australian news media businesses and digital platforms, specifically Google and Facebook”; following a period of consultation that saw substantial public relations campaigning from Google, Facebook, and other content platforms to question the aims and effectiveness of the proposed code, the NMBC bill was sent to federal Parliament in December 2020. Google and Facebook both threatened to remove their services from Australia, or remove Australian news content from their platforms, if the NMBC passed in its original form. Such threats were regarded by some of the NMBC’s proponents as blatant attempts at “bullying” the Australian government to water down the Code, and in pushing ahead with the debate of the NMBC bill in the Australian Parliament the government essentially sought to call the platforms’ bluff – yet in the morning of 18 February 2021, Facebook followed through on its threats and both removed all content from the Facebook pages of Australian news outlets (and from those of other actors mistakenly classified as providing news), and banned any domestic or international users from publishing or accessing any posts that contained links to Australian news sites. The ban remained in force until 26 February, when urgent negotiations between Facebook and the Australian federal government produced a preliminary solution to the crisis. The Code finally became law on 2 March 2021. This panel reviews these turbulent developments. In combination, the four papers on this panel present a comprehensive and multifaceted picture of the News Media Bargaining Code, its context, and implications.